Association of child's disability status with father's health outcomes in Japan. (December 2021) - Dhungel, Bibha; Tsuguhiko, Kato; Ochi, Manami; Gilmour, Stuart; Kachi, Yuko; Takehara, Kenji
Abstract: Fathers' involvement in childcare has been increasing in recent years. However, very little is known about the health impact on fathers when they are caring for or living with a disabled child. This study aims to understand the psychological distress and subjective health outcomes among fathers living with a disabled child compared to fathers living without a disabled child. Data for this study were obtained from the Comprehensive Survey of the Living Conditions conducted by the Ministry of Health, Labour and Welfare in 2016. Multivariable logistic regression was used among 438 disabled-child and father dyads and 27, 682 non-disabled-child and father dyads to analyse the association between a child's disability status with father's health outcomes. Fathers of disabled children had a higher prevalence of psychological distress (17% vs. 12%) and poor subjective health status (13% vs. 8%) than fathers of non-disabled children. A large proportion of disabled children were boys (70%) and had disability level 1 (47%). After adjusting for covariates, the odds ratio (OR) of having psychological distress (OR, 1.53; 95% CI, 1.19–1.97) and poor subjective health status (OR, 1.78; 95% CI, 1.34–2.36) among fathers of disabled children is significantly higher compared to fathers of non-disabled children. Unemployed fathers had a higher odds ratio of psychological distress (OR, 3.07; 95% CI, 2.49–3.79) and poor subjective health status (OR, 4.90; 95% CI, 3.95–6.09) compared to regular working fathers. Fathers of children with disabilities need greater physical and mental health and wellbeing support. They should be provided with additional support not just for their mental but also their subjective wellbeing. Highlights: Fathers of disabled children have higher odds ratio of psychological distress. Fathers of disabled children have higher odds ratio of poor subjective health status. 70% of disabled children were boys and 47% had mildest severity of disability.